The Future of Financial Systems in the Digital Age Perspectives from Europe and Japan - Heckel, Markus; Waldenberger, Franz (Perspectives in Law, Business and Innovation, 2022)
This book is open access, which means that you have free and unlimited access. The increasing capacity of digital networks and computing power, together with the resulting connectivity and availability of "big data", are impacting financial systems worldwide with rapidly advancing deep-learning algorithms and distributed ledger technologies. They transform the structure and performance of financial markets, the service proposition of financial products, the organization of payment systems, the business models of banks, insurance companies and other financial service providers, as well as the design of money supply regimes and central banking. This book, The Future of Financial Systems in the Digital Age: Perspectives from Europe and Japan,brings together leading scholars, policymakers, and regulators from Japan and Europe, all with a profound and long professional background in the field of finance, to analyze the digital transformation of the financial system. The authors analyze the impact of digitalization on the financial system from different perspectives such as transaction costs and with regard to specific topics like the potential of digital and blockchain-based currency systems, the role of algorithmic trading, obstacles in the use of cashless payments, the challenges of regulatory oversight, and the transformation of banking business models. The collection of chapters offers insights from Japanese and European discourses, approaches, and experiences on a topic otherwise dominated by studies about developments in the USA and China.